2012
DOI: 10.4236/abb.2012.38143
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide leads to cytoskeletal reorganization in the retinal pigment epithelium under oxidative stress

Abstract: Light is a risk factor for various eye diseases, including age-related macular degeneration (AMD) and retinitis pigmentosa (RP). We aim to understand how cytoskeletal proteins in the retinal pigment epithetlium (RPE) respond to oxidative stress, including light and how these responses affect apoptotic signaling. Previously, proteomic analysis revealed that the expression levels of vimentin and serine/threonine protein phosphatase 2A (PP2A) are significantly increased when mice are exposed under continuous ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 47 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…Our unbiased proteomic approach demonstrated that actin, tubulin, and vimentin filaments were changed dramatically in the RPE and retina under oxidative environment [2, 3, 6]. Oxidants disrupt barrier integrity and cell junction to initiate the RPE pathogenesis through a blood-retina barrier degeneration mechansim.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our unbiased proteomic approach demonstrated that actin, tubulin, and vimentin filaments were changed dramatically in the RPE and retina under oxidative environment [2, 3, 6]. Oxidants disrupt barrier integrity and cell junction to initiate the RPE pathogenesis through a blood-retina barrier degeneration mechansim.…”
Section: Resultsmentioning
confidence: 99%
“…Balance between actin filaments, intermediate filaments, and microtubules regulates RPE cytoskeleton, mitochondrial morphology as well as mitochondrial traffic. Vimentin phosphorylations induce disassembly of intermediate filaments in vitro [6, 19]. Melatonin is synthesized nocturnally to protect the retina and a potential therapy for retinal diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prohibitin is involved in cell cycle regulation and apoptosis 6 by interacting with the retinoblastoma tumor suppressor protein Rb [7]. Prohibitin plays a major role in C-Raf activation for epithelial cell adhesion and migration [8]. Oxidative stress-induced implications during mitochondrial biogenesis, disruption of mitochondria-nuclear communication, and damage to the mitochondrial DNA (mtDNA) lead to the development of diabetic retinopathy (DR) [10,11,12].…”
Section: Discussionmentioning
confidence: 99%